2022
DOI: 10.1039/d2gc00867j
|View full text |Cite
|
Sign up to set email alerts
|

Efficient utilization of carbon to produce aromatic valencene in Saccharomyces cerevisiae using mannitol as the substrate

Abstract: As a promising brown macroalgae carbohydrate, mannitol has been an alternative renewable feedstock for biofuel and biochemical production, avoiding competition with food production for natural resources. In this study, we...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…13 Although the theoretical yield of LA is 1.0 g/g glucose, in the context of the metabolic background in S. cerevisiae, the energy and redox equivalent requirements need to be considered. 36 In reality, the yield of LA using S. cerevisiae as a host is much lower than the maximum theoretical yield. Several studies have been reported to produce LA under low-pH conditions (Table 1); however, a low concentration of neutralizer is still needed during LA production.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Although the theoretical yield of LA is 1.0 g/g glucose, in the context of the metabolic background in S. cerevisiae, the energy and redox equivalent requirements need to be considered. 36 In reality, the yield of LA using S. cerevisiae as a host is much lower than the maximum theoretical yield. Several studies have been reported to produce LA under low-pH conditions (Table 1); however, a low concentration of neutralizer is still needed during LA production.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although the theoretical yield of LA is 1.0 g/g glucose, in the context of the metabolic background in S. cerevisiae, the energy and redox equivalent requirements need to be considered . In reality, the yield of LA using S.…”
Section: Resultsmentioning
confidence: 99%
“…Mannitol, a major component of brown seaweed, is considered as a sustainable and efficient carbon source due to its wide availability and high reducing power yielded per carbon during the process of mannitol metabolism. 10 In addition, mannitol is a nonfermentable carbon source for S. cerevisiae, meaning it works in a respiration-dependent manner without causing the Crabtree effect and ethanol overproduction (Figure 1). Considering the effect of climatic factors on the sugar content in seaweed, 22 seaweeds from two distinct regions of China, namely, Shandong Province and Fujian Province, were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Significant progress has been made in developing microbial cell-based platforms, such as S. cerevisiae, for valencene production. , While glucose has traditionally been utilized as the carbon source for valencene production, the pioneering work of Zhu et al has shown that high yields of valencene can be achieved using mannitol instead, which presents new opportunities for utilizing seaweed biomass in valencene production.…”
Section: Introductionmentioning
confidence: 99%
“…The final engineered strain yielded 1.2 g L −1 of valencene. A similar study was also reported by Zhu et al, 81 yielding 5.61 g L −1 valencene. Surprisingly, Ye et al 82 also engineered S. cerevisiae to produce a high level of (+)-valencene.…”
Section: Chemical Synthesismentioning
confidence: 99%